The Effect of Drill and Elementary Training to Forehand Ability of Tennis Athletes - Lazuardy Akbar Fauzan (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2022)
Tennis athletes really need to master the forehand stroke well. A quality forehand technique will give athletes high confidence to be able to play tennis wellThis study aims to determine the effect of drill and elementary exercises in improving the forehand hitting ability of JPOK tennis athletes. The research method used is experimental. The study was conducted as many as 16 times the exercise. The subjects in this study were JPOK student tennis athletes, totaling 16 people. The sampling technique used is total sampling. The research instrument used was the Hewitt tennis achievement test to determine the forehand ability. Analysis of research data using t-score analysis to test the difference in the pre-test and post-test scores. The level of validation value is 0.63 and the level of reliability value is 0.75. The results of this study that both drill and elementary training methods can improve the forehand hitting ability of JPOK tennis athletes. The results of data analysis, drill exercises obtained t-count is greater than t-table 17.60 > 2.365. Forehand only effect, t-count is greater than t-table 8.05 > 2.365. Drill and elementary training methods can be used as exercises to improve tennis athletes' forehand skills. Drill training is known to have more effect on tennis forehand ability